Regeneration of a wide range of African cassava genotypes via shoot organogenesis from cotyledons of maturing somatic embryos and conformity of the fieldestablished regenerants - Hankoua, B.; Ng, S.; Fawole, I.; Puonti-Kaerlas, J.; Pillay, M.; Dixon, A. (Springer, 2005)
Genotypic differences in the ability of immature leaf lobes and apical shoot meristems of cassava to form primary somatic embryos in P-CIM were observed (p ≤ 0.05). The mean number of apical meristems forming primary organized embryogenic structures when cultured in embryo induction medium supplemented with picloram (P-CIM) had greatest variability between genotypes (C.V.=22.70%). Maturation frequencies of primary embryos were genotype-dependent and ranged from 17 to 100%. Secondary embryo formation was also genotype-dependent and their maturation frequencies varied from 48 to 100%. Cyclic somatic embryogenesis was successfully established and maintained in 11 genotypes in P-CIM. All genotypes underwent organogenesis with significant genotypic variation (p ≤ 0.05), and organogenic potential ranging from 5.4 to 76.8%. The number of somatic cotyledons forming multiple shoot buds or more than 10 shoot buds per cluster had the greatest variability between genotypes (C.V.=36.96%) as compared with the overall embryogenic potential. Shoot regeneration ability was neither related to primary embryogenic potential nor to explant type for primary embryo induction. Plantlet regeneration per responding explant ranged from 0.1 to 12. Regenerants established in the field at the frequency ranging from 60 to 100%. DNA content of regenerants was homogeneous and similar to that of mother plants and ploidy level was unchanged (2n = 36). The potential benefits of a systematic tissue culture approach for screening agronomically superior genotypes for regeneration capability and its usefulness in selecting those suited for transgenic programs are discussed.